FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BUANG AIR BESAR SEMBARANGAN (BABS) DI DESA KAMPUNG DALAM KABUPATEN LABUHAN BATU TAHUN 2023 - Ginting, Johannes Bastira; -, Hariani; Siagian, Masryna; -, Hartono; Suci, Tri (Jurnal Maternitas Kebidanan, 2024)
Environmental sanitation encompasses housing, sewage disposal, and clean water supply, all crucial to health. A healthy environment sustains the ecosystem, while a poor one leads to sanitation issues and disease spread. The STBM program in Indonesia aims to empower communities to reduce open defecation, though challenges in improving sanitation access persist. This study explores the factors influencing open defecation and provides recommendations for enhancing sanitation and environmental health. The research, conducted in Kampung Dalam Village, Bilah Hulu Sub-district, Labuhan Batu Regency, North Sumatra, began in January 2023. An initial survey found that 96 households lacked healthy latrines. The study used a quantitative cross-sectional design with a sample of 50 households, determined using the Lameshow formula and selected through Simple Random Sampling (SRS). Independent variables included knowledge, attitude, economic status, and facilities (healthy restrooms), while the dependent variable was open defecation behavior. Data collection involved questionnaires and direct interviews with respondents, analyzed using univariate and bivariate methods and the Chi-Square test with a 95% confidence level. The Chi-Square test results showed significant relationships between open defecation behavior and knowledge (p=0.019), attitude (p=0.001), economic status (p=0.009), and facilities (p=0.002) with p-values ≤ 0.05. The study concluded that while knowledge and attitude are linked to open defecation behavior, they do not always directly influence it, suggesting other factors like environment and facilities also play a role. Lower economic status was more often associated with open defecation, and better facilities and access contributed to reduced open defecation behavior.